Effectiveness of a Brief Intervention based on Motivational Interviewing in Colombian Adolescents - Reyes-Rodríguez,Maria Fernanda (2017)
ABSTRACT Prevention science has identified evidence-based strategies for reducing alcohol and other drug use among adolescents, such as Brief Interventions (BI) and Motivational Interviewing (MI). However, there is little evidence about the effectiveness of these practices in Colombia. This study aimed to analyze the effectiveness of the preventive program Brief Intervention based on Motivational Interviewing (BIMI) in reducing alcohol use in adolescents. The program was administered to 3,159 secondary students through a within-subjects design. The results showed that BIMI is a preventive strategy that diminishes the frequency and quantity of alcohol consumption. The study examines how the elapsed time between sessions influences the results. Implications for prevention and evaluation methodologies are discussed.